THE EFFECTIVENESS OF THE IMPACT OF THE METHOD OF INDIVIDUALIZING LEARNING ACCORDING TO THE VARIOUS MEANS OF COMPETITION IN THE PERFORMANCE OF THE TWO SKILLS OF SUPPRESSION AND ROLLING IN AND THE ACCURACY OF SCORING FOR FUTSAL PLAYERS - Dr. Noor Sabah Las (Galaxy International Interdisciplinary Research Journal, 2023)
The research aims to apply learning and identify the impact of this learning on the skills of suppression and dribbling and the accuracy of scoring in football halls, and then identify the impact of the effectiveness of the method of individualizing learning according to the multimedia learning media and on learning in order to reach the desired goals and the extent to which they enhance appropriate learning opportunities through the advantages of this style of learning.